2015
DOI: 10.3233/bme-151320
|View full text |Cite
|
Sign up to set email alerts
|

Improved walking ability with wearable robot-assisted training in patients suffering chronic stroke

Abstract: Abstract. Wearable robotic devices provide safe and intensive rehabilitation, enabling repeated motions for motor function recovery in stroke patients. The aim of this small case series was to demonstrate the training effects of a three-week robotic leg orthosis, and to investigate possible mechanisms of the sensory-motor alterations and improvements by using gait analysis and EMG. Three survivors of chronic strokes participated in robot-assisted gait therapy for three weeks. EMG signals from the rectus femori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…In contrast to studies with patients with SCI, studies with post-stroke patients assessed the gait performance, without wearing exoskeleton, after training with the exoskeleton and compared the results with the baseline measurements. In general, we found that the degree of mobility improvement was not as substantial as with the studies focusing on SCI patients: 12 out of 16 studies analyzing gait speed reported an improvement [37,47,87,102,[105][106][107][108][109][110][111][112], and only 3 out of 9 studies analyzing Flugl-Meyer scores reported an improvement [102,109,112]. Regarding the group of studies focusing on other pathologies, 4 out of 7 studies analyzing outcome measures related to gait speed reported an improvement [36,86,113,114].…”
Section: Performance Assessmentmentioning
confidence: 63%
“…In contrast to studies with patients with SCI, studies with post-stroke patients assessed the gait performance, without wearing exoskeleton, after training with the exoskeleton and compared the results with the baseline measurements. In general, we found that the degree of mobility improvement was not as substantial as with the studies focusing on SCI patients: 12 out of 16 studies analyzing gait speed reported an improvement [37,47,87,102,[105][106][107][108][109][110][111][112], and only 3 out of 9 studies analyzing Flugl-Meyer scores reported an improvement [102,109,112]. Regarding the group of studies focusing on other pathologies, 4 out of 7 studies analyzing outcome measures related to gait speed reported an improvement [36,86,113,114].…”
Section: Performance Assessmentmentioning
confidence: 63%
“…Byl et al [43], observed no adverse events during their study, which was a case series in stroke patients. Other studies with the same device [44][45][46] did not report adverse events related to the use of the device. When the MAK device was used, the participants did not need any additional assistance aside from the assistance that they typically used (such as a cane or crutches).…”
Section: Discussionmentioning
confidence: 97%
“…Existing research on o-RAGT in subjects post stroke is limited, with the patient’s status assessed using a traditional approach based on clinical ordinal rating scales [ 8 ]. Although the clinical effects of o-RAGT in neurological subjects are encouraging [ 7 , 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], the instrumental assessment of gait biomechanics and muscle activations is a necessity to further understand the effects of this rehabilitation approach [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%